Ecocriticism Concepts in The Voices of Marrakesh : A Record of Visit by Elias Canetti - Safitri, Nurul; Ariani, Setya; Sudirman, Eka Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The field of ecocritical literary studies has consistently advanced alongside the deepening comprehension of the link between people and the natural environment. The research aims to analyze the representation of human-environment relationships depicted in The Voices of Marrakesh: A Record of a Visit travel writing by Elias Canetti, employing Greg Garrard’s ecocritical framework. Several key concepts of ecocriticism are presented such as pollution, pastoral, wilderness, apocalypse, dwelling, animals, and the Earth. These representations were explored through qualitative content analysis in travel writing, as one of the forms of literature. The result of this research shows three representations concerning pastoral, wilderness, and dwelling issues. The interconnection between human and natural environment is portrayed as being strongly influenced by cultural, emotional, and spatial experience.Keywords: ecocriticism, human, natural environment, travel writing